Exploratory survey research of providers’ use of continuing professional education methods in accredited Illinois minimum continuing legal education - Fisher, Michael Joseph (Kansas State University, 2021)
This study explored continuing professional education (CPE) methods used by continuing legal education (CLE) providers to meet accreditation standards of the Minimum Continuing Legal Education Board of the Supreme Court of Illinois and recommended standards to expand provider use of CPE methods. The researcher and regulator sent a 21-question survey to 1,872 CLE providers, of which 438 (23%) answered specific questions addressing the overarching research questions: 1) “Are providers using CPE methods to meet the standards?”, 2) “What CPE methods beyond those required by the standards do providers use?”, and 3) “Which provider demographics are predictive of CPE methods used?” Findings from the quantitative analysis showed providers generally used CPE methods adhering to accreditation standards. The statistical analysis indicated larger, commercial providers’ more frequent use of advanced CPE methods including technological program delivery and online interactivity among learners and experts. Employers, when planning and evaluating in-house programs, more frequently used business objectives, developmental benchmarks, competency models, on-the-job observations or attorney performance ratings. Professional associations more frequently used members’ feedback for program improvements. A prior study by Fisher (2017) used a similar version of the survey instrument with another state’s regulator, and had similar recommendations, including how further research may influence the profession to adopt more advanced CPE methods in its standards, shifting from traditions of in-person lecture, and moving beyond a focus on attorney compliance. The legal profession is influential in government, policy, regulation, and societal conduct. With greater awareness of CPE methods, the bar may enhance its practices, while also advancing adoption of CPE methods through regulation of other professions.
Keywords: Legal profession; American Bar Association ABA Model Rule for MCLE; Continuing professional education CPE; Mandatory continuing legal education MCLE; State MCLE boards and commissions; Minimum Continuing Legal Education MCLE Board of the Supreme Court of Illinois